Interplay Between Nanoplastics and the Immune System of the Mediterranean Sea Urchin Paracentrotus lividus - Murano, Carola; Bergami, Elisa; Liberatori, Giulia; Palumbo, Anna; Corsi, Ilaria (Frontiers in Marine Science, 2021)
The present study highlights for the first time the interplay between model nanoplastics, such as the carboxyl-modified polystyrene nanoparticles (PS-COOH, 60 nm) NPs and the coelomocytes of the sea urchin Paracentrotus lividus, a benthic grazer widely distributed in Mediterranean coastal area, upon acute in vitro exposure (4 h) (5 and 25 μg mL–1). Insight into PS-COOH trafficking (uptake and clearance) and effects on immune cell functions (i.e., cell viability, lysosomal membrane stability, and phagocytosis) are provided. Dynamic Light Scattering analysis reveals that PS NP suspensions in CF undergo a quick agglomeration, more pronounced for PS-COOH (608.3 ± 43 nm) compared to PS-NH2 (329.2 ± 5 nm). However, both PS NPs are still found as nano-scale agglomerates in CF after 4 h of exposure, as shown by the polydispersity index > 0.3 associated with the presence of different PS NP size populations in the CF. The observed changes in ζ-potential upon suspension in CF (–11.1 ± 3 mV and –12.1 ± 4 mV for PS-COOH and PS-NH2, respectively) confirm the formation of a bio-corona on both PS NPs. Optical fluorescence microscopy and fluorimetric analyses using fluorescently labeled PS-COOH (60 nm) reveal a fast uptake of PS-COOH primarily by phagocytes within 1 h of exposure. Upon transfer to PS NP-free CF, a significant decrease in fluorescence signal is observed, suggesting a fast cell clearance. No effect on cell viability is observed after 4 h of exposure to PS-COOH, however a significant decrease in lysosomal membrane stability (23.7 ± 4.8%) and phagocytic capacity (63.43 ± 3.4%) is observed at the highest concentration tested. Similarly, a significant reduction in cell viability, lysosomal membrane stability and phagocytosis is found upon exposure to PS-NH2 (25 μg mL–1), which confirms the important role of surface charges in triggering immunotoxicity. Overall, our results show that, although being quickly internalized, PS-COOH can be easily eliminated by the coelomocytes but may still be able to trigger an immune response upon long-term exposure scenarios. Taking into account that sediments along Mediterranean coasts are a sink for micro- and nanoplastics, the latter can reach concentrations able to exceed toxicity-thresholds for marine benthic species.